Promotion Strategies in Sharia Marketing Management: Concepts, Implementation, and Relevance in the Digital Age - Himah Naely; Dwi Novaria Misidawati (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2026)
The development of the halal industry in Indonesia has driven an increase in the need for marketing practices that are not only effective but also in line with sharia principles. Promotion, as one of the main elements in marketing management, has a strategic position in building communication between producers and consumers. However, the dynamics of the digital era present new challenges in the form of rampant manipulative and non-transparent promotional practices that have the potential to violate the principles of honesty and Islamic ethics. This study aims to analyze the concept, form, and implementation of sharia promotion in the context of modern marketing, particularly in the digital environment. The research uses a descriptive qualitative approach with a literature study method on various academic sources regarding sharia marketing, promotional ethics, and digital marketing communication. The results of the analysis show that sharia promotion is based on the principles of shidq (honesty), amanah (trustworthiness), justice, and the prohibition of tadlis (deception) and gharar (uncertainty). In digital practice, the implementation of sharia promotion emphasizes product information transparency, the use of ethical influencers, visual content that is polite and in accordance with Islamic values, and the prohibition of manipulative strategies such as false claims or fictitious discounts. The study also emphasizes that sharia promotion has important relevance for the sustainability of modern halal businesses because it can increase consumer trust and strengthen brand reputation. minimizing the risk of regulatory violations, as well as increasing the competitiveness of Indonesia's halal industry in the global market. Thus, the promotion of sharia is not only an ethical guideline, but also a competitive strategy that is able to respond to contemporary market needs. Keywords: Sharia Promotion; Halal Marketing; Islamic Business Ethics; Tadlis; Gharar; Digital Marketing; Influencer Marketing; Halal Product Guarantee System (SJPH); Consumer Trust; Halal Industry.